The Potential of Implementing Videotaped OSPE Assessment in Health Sciences - Vinodhkumar, Ramalingam; Pradeep, Balakrishnan; Wong, Ling Shing; Sankara, Kumaran Pandian; Chidambaram, Rajavannian; Sinouvassane, Djearamane (Psychology and Education, 2020)
Objective Structured Practical Examination (OSPE) is the mostly practiced method for assessing the practical skills among health science students. OSPE is considered as a reliable method to examine the competency level of the students through the assessment using numerous practical stations. The lack of adequate number of qualified examiners and the fatigue of examiners during the long-term OSPE session are the common challenges faced in the conventional OSPE. Recently the focus is on the videotaped OSPE as an alternative to conventional OSPE to overcome the challenges faced. However, the consistency in marking the videotaped OSPE needs to be validated. Hence, the present study was aimed to study the consistency in marking the videotaped OSPE of 15 health science students by three examiners including 2 internal examiners and 1 external examiner using a content validated rubrics. The results of the present study revealed that the awarded scores were found to be consistent among all three examiners as the statistical analysis showed no significant difference (p>0.05) between the scores conferred by the examiners for the majority of the assessed components. The present study findings suggest that the videotaped OSPE is an alternative reliable and feasible method to assess the practical skills of the health science students. The practice of videotaping the OSPE procedures can overcome the challenges faced during the conventional OSPE such as the non-availability of the qualified examiners and the fatigue of the examiners. Further, the videotaping method gives an opportunity to have more number of practical stations for better assessment on students’ skills and to archive the videotaped practical procedures as an evidence of students’ performance. Hence, the videotaping of OSPE can be a feasible method for the online assessment especially during the pandemic situations like the present Covid-19 pandemic.